From experience to loyalty: Insights from Indonesian fashion e-commerce - Seasylia Marcer Gunawan; Siti Rahayu; Fitri Novika Widjaja (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
The rapid growth of internet use has transformed shopping behavior in Indonesia, particularly in the fashion e-commerce sector. Increasing competition requires online platforms to enhance user experience and electronic service quality to sustain customer satisfaction and loyalty. This study examines the effects of user experience and electronic service quality on customer satisfaction and loyalty in Indonesia’s online fashion industry. Data were collected from 285 respondents who had purchased fashion products through the official websites of five top brands: Adidas, Nike, Converse, H&M, and Uniqlo. Using the disjoint two-stage Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the results reveal that user experience significantly affects electronic service quality and satisfaction, while electronic service quality positively influences satisfaction. Customer satisfaction strongly predicts loyalty. Furthermore, both electronic service quality and customer satisfaction play significant mediating roles. User experience indirectly enhances satisfaction through electronic service quality and indirectly promotes loyalty through satisfaction. This study validates an integrated model in Indonesia’s fashion e-commerce context using a two-stage analytical approach.Keywords: Customer loyalty; Customer satisfaction; E-service quality; E-commerce; User Experience